(untitled) (Revista Espinhaço, 2020)
This study aims to identify the presence of population and human infrastructure in protected areas in the Metropolitan Region of Vale do Paraíba and Litoral Norte (RMVPLN). The study was supported by the use of a new base of statistical sapatial data from the Demographic Census and remote sensing data as nighttime light dataset, through an auxiliary representation to characterize the metropolitan space and its different territories. The analysis was constructed from Occupation Typologies based on the integration of population information, nighttime lights and protected areas, and the results showed a preliminary diagnosis of potential conflicts between local needs, as was the case analyzed at Campos do Jordão Park, site chosen for remote verification of Typologies. These areas need to be detailed and verified in the context of metropolitan planning to considered the regional heterogeneity and specificities of each territories that form the RMVPLN.